Ideologies and crime: political ideas and the dynamics of crime control. Issue 3 (1st October 2016) - Loader, Ian; Sparks, Richard
Abstract : This article assembles some theoretical resources for a project that investigates the ways in which thinking about politics has since the 1970s been bound up with thinking and action around crime. Such investigation is hampered by a dominant (neoliberal) narrative of governance that tends to reduce crime policy to a 'contest' between tactics and technique. In contrast, we establish a political framework for theorising crime and its control. This framework calls for close interpretive analysis of the ways in which disputes about the crime question are always in part contests between different political ideologies and the meaning and significance of their defining concepts. By revisiting penal developments of recent several decades with these questions in mind, one can get closer to the heart of what is at stake when crime is being discussed and acquire a better sense of why crime and its control are legitimately the subject of politics.